CULINARY PRACTICES IN UTTAR PRADESH AND THE IMPACT OF GLOBALIZATION - Gaur, Abhishek; Gupta, Aarti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food is the most basic necessity for every living being, be it human or animal. Food provides energy and nutrients that allow us to grow and stay healthy. Without a nutritious diet, no one would be able to work or play. This study is based on the dietary habits of Uttar Pradesh. Uttar Pradesh is a state in northern India with a population of 19.98 million people. It is the most populous state in India, with 18 subdivisions and 75 districts, and is also the most populous subdivision in the world. This study focuses on the culinary practices of different districts of modern Uttar Pradesh as well as the impact of globalization. This is a chronological study of the eating habits of Indian people, with focus on the most populous state of the country, Uttar Pradesh, and the study is confined to the historical and social factors defining food preferences. The methodology of this study is historical and qualitative. The research is dependent on both primary and secondary sources, such as government annual reports and gazetteers. Uttar Pradesh is the largest producer of several crops like wheat and sugarcane and one of the largest producers of rice, maize, pulses and milk products etc. The culinary culture of Uttar Pradesh grew with the invasion of the Mughals in the sixteenth century as they were very fond of tasting different types of cuisines and hence they brought with them many cooks from Central Asia. These cooks gave birth to a very famous and delicious cuisine i.e. Mughlai cuisine with the help of local Indian cooks and ingredients and that Mughlai cuisine gave birth to the local cuisines of Uttar Pradesh like Awadhi cuisine, Moradabad cuisine, Rampur cuisine etc. Uttar Pradesh cuisine is characterized by a lot of ingredients, spices and the goodness of ghee and mustard oil and its slow cooking is what makes this cuisine very special. The use of mawa, khoya, dry fruits and whole spices makes the cuisine of Uttar Pradesh very rich and delicious.